Diagnosis and treatment of autoinflammatory diseases in adults: a clinical approach from rheumatologists. Issue 4 (2nd October 2018) - Koga, Tomohiro; Kawakami, Atsushi
Abstract: Autoinflammatory diseases are characterized by recurrent systemic inflammation due to dysfunction of the innate immune system, and they are originally the hereditary recurrent fever syndromes that develop in early childhood. Many cases are thus diagnosed in the pediatric field, but there are many cases that are not diagnosed until adulthood, including adult-onset cases. Accordingly, not only pediatricians but also rheumatologists and primary care physicians play a major role in the diagnosis and treatment of autoinflammatory diseases. Broad non-hereditary autoinflammatory diseases such as adult-onset Still disease and Behcet's disease are also often encountered in routine internal medicine practice. With recent developments in genetic testing, the conditions of patients who have been diagnosed and treated as having fevers of unknown etiology have been increasingly classified as autoinflammatory diseases. Regarding treatment in Japan, biological agents (such as canakinumab) that inhibit IL-1β are now administered to patients with autoinflammatory diseases. In this review, we introduce an approach from rheumatologists based on diagnoses and treatment of 'classical" autoinflammatory diseases in adults, focusing on familial Mediterranean fever, which has a high frequency in adults.